Marine Organisms as a Rich Source of Biologically Active Peptides - Macedo, Maria Wanna Figueiredo Sena; Cunha, Nicolau Brito da; Carneiro, Juliana Araújo; Costa, Rosiane Andrade da; Alencar, Sergio Amorim de; Cardoso, Marlon Henrique; Franco, Octávio Luiz; Dias, Simoni Campos (Frontiers in Marine Science, 2021)
Oceanic environments are one of the largest sources of bioactive molecules, due to the high degree of biodiversity and the innumerable ecological relationships established between macro and microorganisms found in the different ecosystems of these complex environments. Marine organisms are being studied increasingly because they are considered important producers of biologically active peptides. Peptides extracted from marine sources have different functions and structures, when compared to peptides isolated from terrestrial sources, considering the different adaptive pressures undergone by these organisms throughout the evolutionary process. Most bioactive compounds isolated from marine environments are obtained from symbiont microorganisms. Of these microorganisms, bacteria are an important source of bioactive peptides, isolated by metagenomic studies from complex gene networks expressed under marine conditions. Several peptides have been shown to have biotechnological properties such as antimicrobial, antitumor, antihypertensive, anticoagulant, anti-fouling and antioxidant activity and can be used in the pharmaceutical and food industries. This review article aims to provide an overview of peptides of biotechnological importance, isolated from different phyla of marine organisms, examining the relationship between structure and function of some of these peptides, as well as the ways of extracting, purifying and prospecting new peptides by traditional methods of isolation or sequence analysis in databases. It also intends to list the peptides that are already being produced and used by the industry, in its various branches, and their current state in the market and in clinical tests.